函数f(x)=x2+2x-5,则f(x-1)等于()
A: x2-6
B: x2-5
C: x2-2x-6
D: x2-2x-5
A: x2-6
B: x2-5
C: x2-2x-6
D: x2-2x-5
举一反三
- 青书学堂: 二次型 f( x 1 , x 2 , x 3 )=2 x 1 2 +5 x 2 2 +5 x 3 2 +4 x 1 x 2 −8 x 2 x 3 ,则 f的矩阵为 。
- 函数$f(x)={{(x+2)}^{2}}{{(x-1)}^{3}}$的极值点是( )。 A: $x=-2$ B: $x=1$ C: $x=-2$ 与 $x=1$ D: $x=-2$ 与 $x=-\frac{4}{5}$
- 函数\(y = {x^{ - 4}}{\rm{ + }}2{x^3} - 2x\)的导数为( ). A: \(4{x^3} + 6{x^2} - 2\) B: \( - 4{x^{ - 5}} + 6{x^2} - 2\) C: \( - 4{x^{ - 3}} + 6{x^2} - 2\) D: \( - 4{x^3} + 6{x^2} - 2\)
- 求方程组的解,取初值为(1,1,1)。[img=250x164]180333307ab8fde.jpg[/img] A: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fsolve(f,[1,1,1],optimset('Display','off')) B: x=fsolve(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1]) C: f=@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3];x=fzero(f,[1,1,1]) D: x=fzero(@(x) [x(1)^3+x(2)-x(3)-5; 2*x(1)+3*x(2)^2-6; x(1)+x(2)+x(3)-3],[1,1,1])
- 求函数$y = {{1 + \root 3 \of {{x^2}} - \sqrt {2x} } \over {\sqrt x }}$的导数$y' = $( ) A: $ {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ B: $ - {1 \over 2}{x^{ - {3 \over 2}}} + {1 \over 6}{x^{ - {5 \over 6}}}$ C: ${1 \over 2}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$ D: ${1 \over 3}{x^{ - {3 \over 2}}} - {1 \over 6}{x^{ - {5 \over 6}}}$